DEVELOPMENT OF PERFORMANCE EVALUATION THEME: A SYSTEMATIC ANALYSIS OF THE LITERATURE - Matos, Lucas dos Santos; Valmorbida, Sandra Mara Iesbik; Martins, Vinicius Abilio; Ensslin, Sandra Rolim (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
This research aimed to identify the development of literature on performance evaluation. It is an exploratory and descriptive research study, with a quali-quantitative approach through bibliometric analysis, using the ProKnow-C intervention instrument. The analyses showed that the main featured article was by Neely, Gregory and Platts (1995). The most influential article in the portfolio was Bourne et al. (2000), with the highest level of betweenness. The Balanced Scorecard is the tool that predominates in 23% of studies; in 30% of the works, was developed by proposing models based on the literature while in 24% of them it was based on a proposal developed by the authors. The study contributed to broaden the knowledge about the subject in order to allow an overview of the literature, when knowing the main authors working on the theme, periodicals, articles, themes, tools and areas of practice. Emerging views on the subject are also presented.